EVALUATION OF CLASSROOM FURNITURE DESIGN ON POSTURE AND MOBILITY OF ELEMENTARY SCHOOL STUDENTS: A SYSTEMATIC LITERATURE REVIEW - Rizky Edbert Setiawan; Kukuh Rizki Satriaji (Jurnal Arsitektur ARCADE, 2026)
Abstract: This study presents a Systematic Literature Review (SLR) examining the interrelationship between classroom furniture design, postural biomechanics, and the mobility of elementary school students. Guided by the PRISMA framework, from an initial pool of 47 peer-reviewed publications, 14 studies met the inclusion criteria and were analyzed in-depth. The review synthesizes the findings into three core domains: macro-environmental demands, physical mismatch crises at the meso-scale, and cognitive ergonomics deficiencies at the micro-scale. Key findings indicate that the implementation of active learning requires dynamic classroom layouts; however, this is hindered by existing furniture standards that demonstrate an absolute mismatch and possess weights exceeding the safe limits of Manual Material Handling (MMH) for children. Furthermore, the analysis reveals a significant research gap regarding affordances, wherein previous furniture designs overlooked the visual cues necessary to guide safe lifting behaviors among children. This study concludes that future furniture design interventions must integrate cognitive ergonomics to mitigate musculoskeletal injury risks while simultaneously supporting a flexible classroom ecosystem aligned with Sustainable Development Goal 4 (SDG 4). Keyword: Affordances, Cognitive Ergonomics, Flexible Seating, Manual Material Handling, School Furniture. Abstrak: Studi ini menyajikan tinjauan literatur sistematis (Systematic Literature Review/SLR) yang mengkaji interelasi antara desain furnitur ruang kelas, biomekanika postur, dan mobilitas siswa sekolah dasar. Dipandu oleh kerangka PRISMA, dari himpunan awal sebanyak 47 publikasi yang ditelaah sejawat, 14 studi memenuhi kriteria inklusi dan dianalisis secara mendalam. Tinjauan ini mensintesis temuan ke dalam tiga domain inti: tuntutan lingkungan makro, krisis ketidaksesuaian (mismatch) fisik pada skala meso, dan defisiensi ergonomi kognitif pada skala mikro. Temuan utama menunjukkan bahwa penerapan pembelajaran aktif menuntut tata letak kelas yang dinamis, namun pelaksanaannya terhambat oleh standar furnitur eksisting yang memiliki tingkat mismatch absolut dan bobot yang melampaui batas aman Manual Material Handling (MMH) anak. Lebih lanjut, analisis mengungkap adanya celah penelitian yang signifikan pada aspek affordances; di mana perancangan furnitur terdahulu mengabaikan petunjuk visual yang diperlukan anak untuk memandu perilaku mengangkat (lifting behavior) secara aman. Studi ini menyimpulkan bahwa intervensi desain furnitur masa depan harus mengintegrasikan ergonomi kognitif untuk memitigasi risiko cedera muskuloskeletal, sekaligus mendukung ekosistem ruang kelas yang fleksibel sesuai dengan Tujuan Pembangunan Berkelanjutan (SDG 4). Kata Kunci: Affordances, Ergonomi Kognitif, Furnitur Sekolah, Manual Material Handling, Ruang Kelas Fleksibel.